Przemiany w sporcie łódzkim po 1956 r - Julian Jaroszewski (Lesya Ukrainka Volyn National University, 2020)
The sport movement along with other aspects of social life was strictly controlled in the communist countries. After Joseph Stalin's death in 1953 the «thaw» was a hope for democratization. On the other hand, a hope for the Polish society appeared in 1956 when, after a wave  of demands and criticism, people enforced the liberalization of home politics. The Head Committee of Physical Culture also believed in the necessity of unavoidable changes. It aimed, however, at the rigid control of the direction and the tempo of the changes by the party apparatus. Although post-October changes followed the mainstream ones, the local specificity can be noticed. They resulted, among the others, from the fact that there existed two committees of physical culture, one in the city of Łódź, the other one in the voivodeship. The process of changes in Łódzkie region was initiated by the national council of sport activists in which regional delegates participated. Both the meeting itself and further changes were scrutinously supervised by party authorities. As a consequence of talks and implemented acts the majority of clubs and associations returned to their traditional names. Sport activists expelled after 1949 were welcome to work in them. This process did not concern all of them. An attempt to reactivate 'Sokół' Gymnastics Association was not approved by party authorities because it was a counter proposition to The Society for the Promotion of Sport and Physical Activity ‒ a unit newly created by the communists. Previous sport sections functioning under The Voivodeship Committee of Physical Culture and Łódzki Committee of Physical Culture, after being combined, reflected county sport unions that were in operation until 1949.